Transient Downregulation of Nanog and Oct4 Induced by DETA/NO Exposure in Mouse Embryonic Stem Cells Leads to Mesodermal/Endodermal Lineage Differentiation - Sergio Mora-Castilla; Juan R. Tejedo; Rafael Tapia-Limonchi; Irene Díaz; Ana B. Hitos; Gladys M. Cahuana; Abdelkrim Hmadcha; Franz Martín; Bernat Soria; Francisco J. Bedoya (Stem Cells International)
The function of pluripotency genes in differentiation is a matter of investigation. We report here that Nanog and Oct4 are reexpressed in two mouse embryonic stem cell (mESC) lines following exposure to the differentiating agent DETA/NO. Both cell lines express a battery of both endoderm and mesoderm markers following induction of differentiation with DETA/NO-based protocols. Confocal analysis of cells undergoing directed differentiation shows that the majority of cells expressing Nanog express also endoderm genes such as Gata4 and FoxA2 (75.4% and 96.2%, resp.). Simultaneously, mRNA of mesodermal markers Flk1 and Mef2c are also regulated by the treatment. Acetylated histone H3 occupancy at the promoter of Nanog is involved in the process of reexpression. Furthermore, Nanog binding to the promoter of Brachyury leads to repression of this gene, thus disrupting mesendoderm transition.